Islamic ethics and the genome question (Studies in Islamic Ethics, 2018)
Islamic Ethics and the Genome Question is one of the very first academic works, which examine the field of genomics from an Islamic perspective. This twelve-chapter volume presents the results from a pioneering seminar held in 2017 at the Research Center for Islamic Legislation andamp; Ethics, College of Islamic Studies, Hamad Bin Khalifa University, in Qatar. The contributors to this volume, coming from different disciplines and specializations, approached the key ethical questions raised by the emerging field of genomics, viz. the Genome Question (GQ), from various angles and perspectives. Their shared thesis is that the breadth and depth of both the GQ and the Islamic tradition necessitate going beyond just producing quick answers in response to immediate questions. In order to accommodate the complexity and wide scope of the GQ, the volume included critical analyses of the ethical discourse on genomics, from outside the Islamic tradition. Within the Islamic tradition, the contributing authors explored how the QG can be better explored by involving insights from various disciplines including Quran exegesis, Islamic jurisprudence, philosophy and theology. Besides its interest for researchers and students specialized in ethics, bioethics and Islamic studies, this volume will be a source of important information for geneticists, genomicists and social scientists who are interested in the ethical discourse about genomics in the Muslim world. Contributors include Arzoo Ahmed, Abbas Amir, Saadia Bendenia, Mohammed Ghaly, Mutaz al-Khatib, Amara Naceur, Aasim I. Padela, Ayman Shabana, Trevor Stammers, Mehrunisha Suleman and Hub Zwart.